Molecular Docking Study of Bioactive Compounds in Senggugu (Clerodendrum serratum (L.) Moon) as Antidiabetics - Rhahmadini, Yahdi Thia; Mulatsari, Esti; Taqwa, Iqbal Ananda; Dhani, Muhammad; Mawijaya, Agus; Susanti, Evi; Simanjuntak, Josua Donrio; Mumpuni, Esti; Prasetiyo, Andri (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2025)
Senggugu has the potential to be a source of natural medicine through its compounds. Using in silico approaches is an effective strategy for exploring compounds from natural products in the screening process. In vivo studies on senggugu have indicated that the plant has antidiabetic activity, although the active compounds involved in this activity are unknown. This study aims to explore the content of bioactive compounds of Senggugu (Clerodendrum serratum (L.) Moon) and its mechanism of action as an antidiabetic in silico with Molegro Virtual Docker software, ChemDraw, visualization with Discovery Studio, and ADMET prediction with pkCSM. The study was conducted by simulating the molecular docking of 31 bioactive compounds in Senggugu (Clerodendrum serratum (L.) Moon) with comparison compounds using glibenclamide, miglitol, rosiglitazone, linagliptin, and empagliflozin. The validated target proteins comprised 5 (five) receptors with PDB ID codes 4YVP, 5NN6, 7AWC, 6Y0F, and 7VSI. Based on this study, the compound predicted to be active as an antidiabetic is [(1S,2S,6R,7S,11R)-11-hydroxy-5,9,13-trimethylidene-4-oxo-3,14-dioxatricyclo [9.2.1.02,6] tetradecan-7-yl]2-methylprop-2-enoate at receptor 4YVP with a rerank score of -107.663 kcal/mol with glibenclamide -94.8299 kcal/mol and [3-hydroxy-4-[(2R)-6-methylhept-5-en-2yl]phenyl]methyl3-methylbut-2-enoate at 5NN6 receptor with a rerank score of -87.8719 with miglitol -64.7212 kcal/mol.